El escenario socioecológico del sistema lagunar costero de Mandinga, Veracruz, México: problemas y conflictos en torno a la conservación ante el avance inmobiliario - Ciprés-Chávez, Adrián; Paradowska, Krystyna; Moreno-Casasola, Patricia; Silva-Rivera, Evodia (Pontificia Universidad Católica del Perú, 2025)
The Mandinga Coastal Lagoon System (MCLS) is in central Veracruz, Mexico. Over the last two decades, an ambitious development project named the Riviera Veracruzana has been implemented, aggravating existing socio-ecological problems. The study analyzed the socio-ecological scenario in this system, characterizing the socio-ecological problems and the social actors involved based on their perceptions, interests and power relations. A two-track methodological scheme was used: (1) collection of information from secondary sources associated with the MCLS and (2) ethnographic data collection with primary sources through semi-structured interviews with key social actors from different social sectors, participatory workshops with focus groups and a field diary. The results revealed a perception of high environmental degradation, socio-ecological conflicts surrounding the conservation and use of territory, and an asymmetry of power among social actors. It is crucial to search for alternatives aiming at power reconfiguration but especially based on people centered, co-produced conservation strategies.

El sistema lagunar costero de Mandinga (SLCM) se encuentra en la porción central costera de Veracruz, México. En las últimas dos décadas, se ha impulsado el proyecto de desarrollo inmobiliario Riviera Veracruzana, generando profundas afectaciones socioecológicas. El objetivo del trabajo fue analizar el escenario socioecológico del SLCM, caracterizando los problemas y los actores sociales involucrados de acuerdo con sus percepciones, intereses y relaciones de poder. Para esta investigación se ocupó una metodología híbrida: (1) de recolección de información de fuentes secundarias asociadas al SLCM, (2) de carácter etnográfico con fuentes primarias, a través de entrevistas semiestructuradas con actores sociales clave de diversos sectores sociales, (3) talleres participativos con grupos focales y (4) diario de campo. Los resultados indican una percepción de alta degradación ambiental, conflictos socioecológicos en torno a la conservación y uso de los espacios, así como una asimetría de poderes entre los actores. Es crucial la búsqueda de alternativas que reconfiguren los poderes y direccionen estrategias participativas de conservación efectivas.
The Social-Ecological Scenario of Mandinga’s Coastal Lagoon System, Veracruz, Mexico: Problems and Conflicts over Conservation in the Face of Real Estate Expansion
Keywords: Conservation; Socio-environmental problems; Power relations; Urbanization; Veracruz Riviera, Mexico; Conservación; Relaciones de poder; Urbanización; Riviera Veracruzana, México; Problemas socioambientales; https://purl.org/pe-repo/ocde/ford#2.07.01